Validation of a single-day maximal lactate steady state assessment protocol - Kuphal, K. E.; Potteiger, J. A.; Frey, B. B.; Hise, M. P. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The classical maximal lactate steady state (MLSS) assessment protocol takes multiple days to measure thus necessitates athletes to return to a laboratory for several visits. The purpose of this study was to assess the validity and reliability of a new protocol (Palmer protocol), which proposes to measure MLSS in a single-day. METHODS: Nine endurance-trained males (age 21.1 +/- 1.6 years, VO2max of 63.2 +/- 3.2 ml x kg(-1) x min(-1)) performed the Palmer protocol and the classical MLSS assessment protocol. The classical MLSS protocol consisted of several constant-velocity runs of increasing intensity. The MLSS was defined as the highest velocity associated with an increase in blood lactate concentration ([La-]) = or < 1.0 mmol x L (-1) during the final 20 min of a 30 min run. Concurrent validity was assessed by calculating a Pearson product correlation coefficient between the running velocity at MLSS from the classical protocol and from the single-day Palmer protocol. Test-retest reliability was assessed by calculating a Pearson product correlation coefficient between the running velocities from 2 separate trials of the single-day Palmer protocol. RESULTS: The velocity at MLSS from the single-day Palmer protocol (236.4 +/- 27.8 m x min(-1)) produced a strong correlation of 0.97 (p<0.001) with the velocity at MLSS from the classical protocol (226.3 +/- 22.6 m x min(-1)). An equally strong correlation was calculated from test-retest reliability of the single-day Palmer protocol (r=0.97), (p<0.001). CONCLUSION: These results suggest that the single-day Palmer protocol is valid and reliable in the estimation of MLSS.